Role of Aquaculture Fisheries Subsector and Determination of Superior Aquaculture Fisheries Commodity to Regional Development in Kediri City, East Java - Titis Nastiti; Anthon Efani; Zainal Abidin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
This research aims to know and analyze about contribution, the role of, multiplier effect, and superior commodity of aquaculture fisheries concerning economics regional in Kediri city. The research method using quantitiative descriptive research. Type of data used are secondary data. The method of collecting data is documentation. Methods of data analysis using shift share, location quotient, and multipler effect. This research indicate that aquaculture fisheries have low contribution to regional economics of Kediri city but the role of them become subsector basic and have multiplier effect too. Superior commodity of aquaculture fisheries have Nila, Mas, Lele, Tawes, Patin, Gurami, Koi, Cupang Manvis, Mas Koki, Plati, Gapi, Moli, and Kar Tetra.